The influence of cold storage on the characteristics of platelet concentrate - Sergey Sidorkevich; Andrey Kasyanov; Tatiana Glazanova; Stanislav Abramovsky; Stanislav Bessmeltsev (Open Journal of Tropical Medicine - Peertechz Publications, 2022)
Introduction: Platelet concentrates (PC) are among the most needed blood components used to correct thrombocytopenia of various origins. The main problems in transfusion therapy are the risks of infectious complications associated with the limited shelf life of platelet concentrates at storage. The article presents the results of a comparative analysis of the quality parameters of apheresis platelet concentrate prepared on two additional solutions: experimental additional solution (ASexp) containing sodium fumarate and SSP+ solution.  Objective: To perform a comparative analysis of quality parameters, metabolic rate, hemostatic ability, and markers of activation and apoptosis of platelets (15 units) prepared on an experimental additional solution containing sodium fumarate and on an additional SSP+ solution for prolonged storage periods (15 days) at a temperature of 4 °C ± 2 °C.  Materials and methods: We have studied the parameters of the thrombography, metabolism, hemostatic potential, markers of activation, and apoptosis for prolonged periods (15 days) of storage at a temperature of 4 °C ± 2 °C.  Results: The results of the study indicate that during prolonged cold storage (15 days), there is a slight decrease in the number of platelets, a decrease in the level of metabolism, and significant morphofunctional changes occur both when using SSP+ and ASexp additional solutions. At the same time, hemostatic activity remains at a fairly high level throughout the entire storage period. The results of the analysis for most of the studied parameters did not reveal significant differences between the groups. At the same time, the parameters mandatory for quality control and safety met the standard values by the end of the observation period.  Conclusion: Our data indicate the possibility of using the developed additional solution based on sodium fumarate for storing platelets at a temperature of +4 °C ± 2 °C for 15 days.